Metabolites and hormones are involved in the intraspecific variability of drought hardening in radiata pine - De Diego, N; Saiz-Fernández, I; Rodríguez, J L; Pérez-Alfocea, P; Sampedro, M C; Barrio, R J; Lacuesta, M; Moncaleán, P (Journal of plant physiology, 2015)
Studies of metabolic and physiological bases of plant tolerance and hardening against drought are essential to improve genetic breeding programs, especially in productive species such as Pinus radiata. The exposure to different drought cycles is a highly effective tool that improves plant conditioning, but limited information is available about the mechanisms that modulate this process. To clarify this issue, six P. radiata breeds with well-known differences in drought tolerance were analyzed after two consecutive drought cycles. Survival rate, concentration of several metabolites such as free soluble amino acids and polyamines, and main plant hormones varied between them after drought hardening, while relative growth ratio and water potential at both predawn and dawn did not. Hardening induced a strong increase in total soluble amino acids in all breeds, accumulating mainly those implicated in the glutamate metabolism (GM), especially L-proline, in the most tolerant breeds. Other amino acids from GM such as γ-aminobutyric acid (GABA) and L-arginine (Arg) were also strongly increased. GABA pathway could improve the response against drought, whereas Arg acts as precursor for the synthesis of spermidine. This polyamine showed a positive relationship with the survival capacity, probably due to its role as antioxidant under stress conditions. Finally, drought hardening also induced changes in phytohormone content, showing each breed a different profile. Although all of them accumulated indole-3-acetic acid and jasmonic acid and reduced zeatin content in needles, significant differences were observed regarding abscisic acid, salicylic acid and mainly zeatin riboside. These results confirm that hardening is not only species-dependent but also an intraspecific processes controlled through metabolite changes.
Keywords: druhová specificita; Plant Breeding; GABA; Pinus; Amino acids; Droughts; Proline; Hardening; šlechtění rostlin; regulátory růstu rostlin; prolin; Phytohormones; Species Specificity; borovice; gamma-Aminobutyric Acid; Plant Growth Regulators; Growth; Polyamines; Pinus radiata; období sucha